Correction to: Systematic analyses reveal long non-coding RNA (PTAF)-mediated promotion of EMT and invasion-metastasis in serous ovarian cancer - Haihai Liang; Xiaoguang Zhao; Chengyu Wang; Jian Sun; Yingzhun Chen; Guoyuan Wang; Lei Fang; Rui Yang; Mengxue Yu; Yunyan Gu; Hongli Shan (Molecular Cancer, 2020)
An amendment to this paper has been published and can be accessed via the original article.